2019
DOI: 10.9775/kvfd.2019.21752
|View full text |Cite
|
Sign up to set email alerts
|

Kuzeybatı Çin’de Atık Koyun Fötuslarından Brucella suis S2 İzolasyonu

Abstract: This study aimed to investigate the cause of abortion in a traditional sheep farm. Here, 31 specimens were examined by PCR targeting the Brucella outer membrane protein gene 22 (omp22), and 25 (80.6%, 25/31) were found to be positive. Totally, 3 Brucella suis S2 and 10 Brucella melitensis were isolated from 31 aborted fetuses in which one B. suis S2 and B. melitensis were isolated from a same aborted fetus. All of these isolates were identified by PCR and conventional bacterial tests. These 3 B. suis isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This disease is characterized by undulant fever and chronic debilitating symptoms, such as endocarditis, spondylitis, arthritis, and meningitis; in livestock, it causes abortion and infertility [2][3][4]. Several studies have shown that Brucella melitensis is the predominant pathogen responsible for human or animal brucellosis in many provinces in China, including Xinjiang, Inner Mongolia, and Shanxi [4][5][6][7][8][9][10][11][12]. However, the pathogenic mechanisms of Brucella are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…This disease is characterized by undulant fever and chronic debilitating symptoms, such as endocarditis, spondylitis, arthritis, and meningitis; in livestock, it causes abortion and infertility [2][3][4]. Several studies have shown that Brucella melitensis is the predominant pathogen responsible for human or animal brucellosis in many provinces in China, including Xinjiang, Inner Mongolia, and Shanxi [4][5][6][7][8][9][10][11][12]. However, the pathogenic mechanisms of Brucella are not well understood.…”
Section: Introductionmentioning
confidence: 99%